Doubly selective multiple quantum chemical shift imaging and T1 relaxation time measurement of glutathione (GSH) in the human brain in vivo. (22nd June 2012) - Choi, In‐Young; Lee, Phil
<x xml:space="preserve">Abstract</x> Mapping of a major antioxidant, glutathione (GSH), was achieved in the human brain in vivo using a doubly‐selective multiple quantum filtering based chemical shift imaging (CSI) of GSH at 3 T. Both in vivo and phantom tests in CSI and single voxel measurements were consistent with excellent suppression of overlapping signals from creatine, γ‐Amino butyric acid (GABA) and macromolecules. GSH concentration in the fronto‐parietal region was 1.20 ± 0.16 µmol/g (mean ± SD, n = 7). The longitudinal relaxation time (T1) of GSH in the human brain was 397 ± 44 ms (mean ± SD, n = 5), which was substantially shorter than that of other metabolites. This GSH‐CSI method permits us to address regional differences of GSH in the human brain under conditions where oxidative stress has been implicated, including multiple sclerosis, aging and neurodegenerative diseases. Copyright © 2012 John Wiley & Sons, Ltd.